Be Active: design and creation of an innovative digital platform for active methodologies (Research, Society and Development, 2022)
The article is an experience report of design and creation of a digital platform for the application of active learning methodologies. There are digital platforms that offer support for the use of active methodologies, however, they usually choose a single methodology and to diversify the strategies, one must use different platforms. In this context arises the Project "Be Active", whose goal is to implement a digital platform in which it is possible to apply and map the learning and performance of students through different active methodologies. The project started in 2019 and is developed through a methodology inspired by the R&D cycle. The production team is multidisciplinary and meets weekly. Initially, a briefing and a delivery map, execution flowchart, and indicators were structured. Currently, Be Active already allows, for any educational model (distance, hybrid, or face-to-face), the support for the use of active methodologies: Problem-Based Learning, Project-Based Learning, Peer Instruction, Team-Based Learning, as well as gamification strategies. In addition, it allows the application of Learning Styles Diagnostics. It allows the user to register and use the methodologies synchronously or asynchronously, as well as reports on student performance that can be downloaded and analyzed qualitatively and quantitatively. The perspective is to improve its functionalities, layout, and usability. It is hoped that it will be possible, through the wide dissemination of the use of the platform, to contribute to a contextualized and innovative educational reality, adapted to a logic of complex and continuous learning.